Generalised hybrid switching topology for a single‐phase modular multilevel inverter. Issue 10 (1st October 2014) - Kaliamoorthy, Mylsamy; Rajasekaran, Vairamani; Christopher Raj, Irudayaraj Gerald; Hubert Tony Raj, Lawrence
Abstract : A modified single‐phase hybrid cascaded H bridge multilevel inverter with a minimum number of power electronic devices and isolated DC sources is presented in this study. It consists of two inverters (upper and lower) coupled in cascade. The lower inverter is capable of developing a multilevel output and switches at low frequency and another inverter develops two‐level output and switches at high frequency. In the proposed inverter, every additional power electronic switch in the lower inverter increases the level by four. This study also introduces a generalised hybrid modulation switching strategy, which gives arithmetical and logical expressions for switching the additional device for any required increase in levels. The voltage rating of the devices, conduction and switching loss of the proposed inverter are compared with the similarly setup topologies. The generalised hybrid modulation algorithm is simulated in MATLAB/Simulink and implemented in a SPATRAN 3A DSP board. Simulation and experimental results are presented for different loading conditions.